LEGAL PROTECTION OF CONSUMERS AGAINST NON-CONFORMITY OF GOODS IN E-COMMERCE TRANSACTIONS : AN ANALYSIS OF BUSINESS ACTORS' RESPONSIBILITIES: English - Muhammad Zidan Rohmatualloh; Ratu Mawar Kartina (Siber Nusantara of Law and Politic Review, 2026)
The development of electronic commerce (e-commerce) in Indonesia has simplified the process of buying and selling goods. However, this has also given rise to many legal issues, particularly those related to discrepancies between the information provided by business actors and the goods received by consumers. This situation causes losses for consumers and requires legal protection. The research questions in this study are as follows: (1) how do Indonesian laws and regulations regulate consumer legal protection against product discrepancies in online transactions; and (2) how are business actors responsible for providing compensation to consumers. The research methodology used in this study is normative legal research, which includes legal and conceptual techniques. Among the legal texts used are Law Number 8 of 1999 concerning Consumer Protection, Law Number 11 of 2008 concerning Electronic Information and Transactions and its revisions, and Government Regulation Number 80 of 2019 concerning Commerce Through Electronic Systems. The analysis uses a qualitative descriptive approach. The study findings indicate that consumer legal protection in e-commerce transactions is governed by preventive and repressive strategies. The obligation of business actors to provide accurate, correct, and transparent information about the products they sell is an example of preventive protection. Customers' rights to refund and dispute resolution processes provide some protection in the meantime. In circumstances of non-conforming items, business actors are liable for replacement goods, refunds, or other comparable compensation, which generally reflects the strict responsibility concept in reality. In conclusion, even while normative legal protection for consumers is thought to be sufficient, its application is still not ideal. This is brought about by inadequate oversight, a lack of understanding among business players, and the intricacy of legal relationships in multi-party e-commerce transactions.